Predictors of Hospital Utilization Among Papuans in Indonesia - Agung Dwi Laksono1, Ratna Dwi Wulandari2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hospitals were advanced referral health facilities or referrals for basic health services, it was very important for policymakers to know the factors that it was able to predict hospital use. The research objective was to determine the predictors of hospital use among Papuans in Indonesia. Data source from raw data of the 2013 Indonesia Basic Health Survey. Indonesia Basic Health Survey was a cross-sectional survey. The multistage cluster random sampling method was used to get 30,620 Papuan respondents. Multinomial Logistic Regression Test is used to determine the predictors of hospital utilization. There were 8 predictors of hospital utilization in outpatients used consisting of age, urban-rural area, gender, education level, socioeconomic status, insurance ownership, travel time and transportation costs, there were 5 predictor variables in hospital utilization in patients hospitalization consisting of gender, type of work, socio-economic status, travel time and transportation costs, and there were 2 predictors in hospital utilization in outpatient and inpatient care at the same time consisting of the cost of time travel and transportation to the hospital. Overall there were 9 predictor variables of hospital utilization in all categories (outpatient and inpatient).